A study on the activities of Minggu Destini Siswa: is improvement needed to enhance its effectiveness? / Alwani Abdul Rahman, Nur Azimah Ahmad Beduwi & Roselina Dian - Abdul Rahman, Alwani; Ahmad Beduwi, Nur Azimah; Dian, Roselina (2011)
There are many stages in our life that required us to accept anything changes and challenges that will come into our life. That is same with student’s life. After finish primary school, the student will continue studies in secondary school and lastly tertiary education. Tertiary educations refer to higher education that include undergraduate and post graduate education. For information, the main institutions that provide tertiary education is colleges, universities, institutes of technology and polytechnics. Through this institution student can get the certificates of diplomas and academic degrees after completely well done their studies in their own field. People always said that there are so many different things that the students must face during the process of tertiary education especially the environments of learning. In short in tertiary institution is more to be independent that is everything is depend on our self. The university environments as explained by Devlin, M (2009).